2018
DOI: 10.5815/ijisa.2018.08.02
|View full text |Cite
|
Sign up to set email alerts
|

Method for Determination of Cyber Threats Based on Machine Learning for Real-Time Information System

Abstract: This work is about the definition of cyber threats in the information system. The cyber threats lead to significant loss of network resources and cause the system disability as a whole. Detecting countermeasures in certain threats can reduce the impact on the system by changing the topology of the network in advance. Consequently, the interruption of a cyberattack forces the intruders to seek for alternative ways to damage the system. The most important task in the information system work is the state of netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…The use of countermeasures for certain threats can reduce the impact on the system. One of the main tasks to prevent or reduce the impact of cyberattacks on information systems is to monitor the state of network equipment and the ability to support network infrastructure during critical situations in working condition [14].…”
Section: Research Resultsmentioning
confidence: 99%
“…The use of countermeasures for certain threats can reduce the impact on the system. One of the main tasks to prevent or reduce the impact of cyberattacks on information systems is to monitor the state of network equipment and the ability to support network infrastructure during critical situations in working condition [14].…”
Section: Research Resultsmentioning
confidence: 99%
“…In addition, many studies [13,20,31,32,33,[35][36][37][38][39], including Kargina [14], have examined the role of information security in the digital economy and have shown that it is a topical issue for the present. Issues such as the significant change in social relations as a result of the use of modern ICT technologies, the existence of a new level of work with data in the digital environment are considered here.…”
Section: Research Of Relevant Related Workmentioning
confidence: 99%
“…The concept of information security is inextricably linked with the concept of cybersecurity [7,8]. World practice knows several concepts of the latter, there is no single generally accepted one.…”
Section: The сOncept Of Cybersecurity and Its Implications For The Aviation Sectormentioning
confidence: 99%